O telhado verde no clima semiárido: um estudo de viabilidade para construições em Pau dos Ferros/RN - Sá, Renê Alexssandro Brito de (Universidade Federal Rural do Semi-Árido, 2018)
According to the current situation of the last civil constructions that the urban centers meet, whereas it affects environmental conditions, as well as associated problems, such as the islands of heat, the present work presents a feasibility analysis of the use of the green roof as an alternative to replace the conventional roofs, composed of asbestos cement and ceramic tiles. The green roof, cover or suspended garden are some of the names given to a construction system where it is possible to apply vegetation indicated for the purpose of the use of the project on top of slabs from the provision of layers of waterproofing and drainage able to sustain the substrate and vegetation, Besides the benefit of the aesthetics of the building, the application of the green roof provides improvements for society and the environment, since it works as a thermal insulation causing better conditions of comfort in built environments. In addition to the increase of green areas in large cities decreased the effects of heat islands and the improvement of air quality.
Keywords: Telhado verde; Sistema construtivo; Vegetação; Green roof; Constructive System; Vegetation; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA